KOMPOSISI KIMIA MINYAK ATSIRI Melodorum cylindricum (Maing. ex Hook.f & 1 Thorns), Litseajirma (Blume) Hook.f., Fl. Brit. Ind. DAN Callistemon lanceolatus D.C. - Yuliasri Jamal (BERITA BIOLOGI, 2009)
Steam distillation of Melodorum cylindricum leaves (176 gram), Litsea firma leaves (295 gram), L firma stem bark (1,590 gram) and Callistemon lanceolatus leaves (300 gram) yielded 0.15%, 1.68%, 0.23% and 0.4% essential oils respectively.The oils were analyzed using GC-MS methods. The results identified 71 components from the leaves of M. Cylindricum which p-myrcene is the highest (12,56%). Leaves and stem bark of L. firma contained 20 and 24 components which 2-undecanone (34,95%) and undecanone (29,57%) as the highest major components. The essential oil of C. lanceolatus identified 24 components and 1,8 cineol is the major component with the highest content, 67.37%.